Assessment of changes in climate extremes of temperature over Ethiopia. Issue 1 (31st December 2023) - Gedefaw, Mohammed
Abstract: Recently, extreme climatic events have been a major concern across the world. Assessments on various climates and geographic regions are needed to understand the uncertainties in extreme climate events' responses to global warming. Developing countries particularly Ethiopia is highly affected by such extreme climate events due to its low adaptive capacity. The aim of this study was to investigate the trends of daily extreme temperatures indices in Ethiopia. The changes and trends in climate extremes of temperature were evaluated based on 14 indices of extreme temperatures over Ethiopia. The Mann-Kendall (MK) trend test is used to investigate the trends in the selected datasets. In the present study, three zones, which represent 34 stations, were selected based of extreme climate indices. The results of 14 extreme temperature indices showed that warm days (TX90p) and nights (TN90p) increased by 2.65 (P < 0.05) and 2.04 (P < 0.05) days/decade, respectively. The annual maximum and minimum temperatures (TXam and TNam) as well as the diurnal temperature range (DTR) were 2.68/decade, 2.04/decade and 0.62/decade, respectively. 73.5% and 26.5% of the stations show an increasing trend for (TXx and TNx), respectively. The extreme hot temperature indices (TXx, TXn, TX90, TN90 and SU) and cold temperature indices (ID, TNn, TXn, TX10P, TN10P and FD) exhibited contrasting variations over the stations. As far as spatial patterns concerned, most of the stations show significant increasing trends in northern and southeastern parts of Ethiopia. Thus, changes in climate extremes will likely increase the risk of severe extreme events and the society to become more vulnerable to the climate shocks. Generally, the findings of this study could help decision and policymakers to take immediate measures to tackle the climate change impacts.